Generative Interactive Psychotherapy Expert (GIPE) bot - Khalaf, Ayesheh Ahrari; Hassan Abdalla Hashim, Aisha; Olowolayemo, Akeem; Olanrewaju, Rashidah Funke (International Journal of Computer Science and Network Security, 2023)
One of the objectives and aspirations of scientists and engineers ever since the development of computers has been to interact naturally with machines. Hence features of artificial intelligence (AI) like natural language processing and natural language generation were developed. The field of AI that is thought to be expanding the fastest is interactive conversational systems. Numerous businesses have created various Virtual Personal Assistants (VPAs) using these technologies, including Apple's Siri, Amazon's Alexa, and Google Assistant, among others. Even though many chatbots have been introduced through the years to diagnose or treat psychological disorders, we are yet to have a user-friendly chatbot available. A smart generative cognitive behavioral therapy with spoken dialogue systems support was then developed using a model Persona Perception (P2) bot with Generative Pre-trained Transformer-2 (GPT-2). The model was then implemented using modern technologies in VPAs like voice recognition, Natural Language Understanding (NLU), and text-tospeech. This system is a magnificent device to help with voicebased systems because it can have therapeutic discussions with the users utilizing text and vocal interactive user experience.